Plasma from hypertensive pregnancy patients induce endothelial dysfunction even under atheroprotective shear stress - Sarah Viana-Mattioli; Miriam Helena Fonseca-Alaniz; Iguaracy Pinheiro-de-Sousa; Ricardo Rosa Junior; Moises Henrique Mastella; Ricardo de Carvalho Cavalli; Valeria Cristina Sandrim (Scientific Reports)
Abstract Preeclampsia (PE) is a challenge in maternal healthcare due to its complex nature, characterized by high blood pressure, protein in the urine, and damage to various organs. There is evidence linking PE to endothelial dysfunction (ED), triggered by substances released from an oxygen-deprived placenta. Previous in vitro studies have not considered the impact of in vivo elements, such as the different patterns of blood flow, and laminar (LSS) vs. oscillatory (OSS) shear stress, on the development of ED. We investigated the impact of plasma from healthy pregnant women (HP), subjects with gestational hypertension (GH), and PE patients on global gene expression of human coronary endothelial cells (HCAECs) under LSS and OSS. Our findings revealed a unique transcriptional profile of endothelial cells induced by plasma incubation in LSS. Notably, OSS resulted in similar transcriptomes irrespective of plasma treatment. Under LSS, GH plasma resulted in a proliferative profile, whereas PE plasma was linked to pro-inflammatory and antioxidant profiles compared to HP plasma. Our findings demonstrate that shear stress levels influence the endothelial cell transcriptome in response to plasma from hypertensive pregnancy patients. Both PE and GH can induce endothelial dysfunction under atheroprotective LSS, with a more significant effect observed with PE-derived plasma.